The Research on Telemetry Modulation System - Wu Guo-Hui; Dai Ji-Yang; Chu Bao-Jun (Institute of Advanced Engineering and Science, 2013)
To develop the effective aerospace telemetry communication system, for aerospace telemetry communication requirements high-speed, high bandwidth, high efficiency and low interference, puts forward the C-WQPSK（C-W Quadrate Phase- Shift Keying）modulation method. This method based on direct carrier QPSK, didn’t consider baseband pulse signal, and redesigned the modulating waveform, its phase angle jump and jump to change duration time all can be changed. Also it gives the C-WQPSK performance and theory analysis, and with QPSK, FQPSK the performance comparison, Through the MATLAB simulation experiment, verify this modulation method is correctness and effectiveness. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2458